THE INFLUENCE OF EWA APPS ON LISTENING SKILLS IN ENGLISH LEARNING: A STUDY OF TENTH GRADE STUDENTS AT SMAN 4 METRO - Najah Mustaghfiroh; Dedy Subandowo; Fenny Thresia (Universitas Muhammadiyah Metro, 2025)
This quasi-experimental study examines the influence and significant influence of the EWA English learning application on the listening skills of tenth-grade students at SMAN 4 Metro. Two classes were designated as an experimental group (using the EWA app in learning) and a control group (using traditional instruction), and both groups underwent pre-test and post-test assessments of listening comprehension. The experimental group’s average listening score improved from 54.14 (pre-test) to 75.72 (post-test), a gain of 21.58 points, whereas the control group’s average score increased from 53.33 to 66.64. Statistical analysis confirmed that score in the experimental group was significantly greater than that of the control group, as indicated by paired-sample and independent-sample t-tests (p < 0.05). Assumption tests verified that the data were normally distributed and had homogeneous variances (Shapiro-Wilk test and Levene’s test, respectively), validating the use of parametric analysis. These findings demonstrate that integrating the EWA app into English learning can significantly influence students’ listening skills compared to conventional teaching methods.